EVALUATION OF SORGHUM SILAGE WITH ADDITIVES – ALTERATIONS IN DRY MATTER, FIBROUS FRACTIONS AND “IN VITRO” DRY MATTER DIGESTIBILITY - ARMANDA COSTA PEREIRA; LÚCIO CARLOS GONÇALVES; ANA LUIZA COSTA CRUZ BORGES; JOSÉ AVELINO SANTOS RODRIGUES; SILAS PRÍMOLA GOMES; IRAN BORGES; NORBERTO MARIO RODRIGUEZ; JAIRO JOSÉ COSTA FERREIRA; LUCAS PAIN DELGADO; MARIANA MAGALHÃES CAMPOS (Revista Brasileira de Milho e Sorgo, 2008)
This work evaluated the fermentation pattern of sorghum silage hybrid BR 601 with and without additives. At ensiling time, silages were enriched with the additives, adopting the following treatments: silages without additive (control), with 0.5% urea, 0.5% limestone, 0.5% urea plus limestone and bacterial inoculant. The materials were stored into PVC silos, opened after 1, 3, 5, 7, 14, 28 and 56 days of ensiling. Alterations were determined in dry matter (DM), neutral detergent fiber (NDF), hemicellulose, cellulose, acid detergent fiber (ADF) and lignin contents and in vitro dry matter digestibility (IVDMD). A completely randomized experimental design was used, in a 5 x 7 factorial scheme, and the means were compared by the SNK test at 5% probability. The silage enriched with urea plus limestone showed highest loss of DM. No difference was observed between silage with additives and control regarding NDF, hemicellulose, cellulose and DMIVD. The additives promoted changes in the ADF and lignin contents.